An Italian Campaign to Promote Anti-doping Culture in High-School Students - Codella, Roberto; Glad, Bill; Luzi, Livio; La Torre, Antonio (Frontiers in Psychology, 2019)
Doping poses a threat to sport worldwide. Studies have revealed that, in addition to elite athletes, amateur and recreational sportsmen and sportswomen are making increasing use of performance-enhancing drugs. Worryingly this trend has been documented among young people. Anti-doping efforts seeking to deter elite athletes from doping through detection of the use of prohibited substances are costly and have not been completely effective either at the top-level or the amateur/recreational level. A thoughtful education program, inspired by honesty and respect, might be more effective in shaping attitudes towards doping in young people and protecting their health. For these reasons, the Italian “Lotta al Doping” (Fight Against Doping) project sought to cause a cultural shift in young people by taking anti-doping seminars to high schools. In the 2017-2018 school year we reached more than 20,800 students from 157 high schools through 202 seminars. Before and after the seminars, we administrated anonymous, voluntarily completed surveys with a set of questions (items = 15), taken from the WADA-Play-True-Quiz. Upon completion of the 2-hour seminar, the majority of the answers given by the students resulted correct (13 out of 15 items, p<0.000001, McNemar) confirming the value of the initiative. This project stands out as promising in the doping prevention process at the youth and amateur levels.